1988
DOI: 10.1042/bj2510553
|View full text |Cite
|
Sign up to set email alerts
|

A tissue-specific increase in lipogenesis in rat brown adipose tissue in hypothyroidism

Abstract: 1. Rats were made hypothyroid by feeding them with propylthiouracil together with a low-iodine diet for 4 weeks. 2. [U-14C]Glucose conversion into fatty acids was substantially enhanced in brown adipocytes isolated from hypothyroid rats. Incorporation of 3H2O into fatty acids in vivo was enhanced in hypothyroidism in interscapular brown fat, but not in epididymal white fat or in liver. Hypothyroidism increased the activities of fatty acid synthase and ATP citrate lyase in brown, but not in white, adipocytes. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…Hypothyroidism causes changes in the handling of long chain fatty acids by white and brown adipocytes. In brown adipocytes fatty acid synthesis from glucose is substantially enhanced in hypothyroidism [25]. In this study, the large clear vacuoles seen in the cytoplasm of brown adipose tissue in the rats were consistent with lipid storage vacuoles, which in turn was consistent with enhanced fatty acid synthesis.…”
Section: Discussionsupporting
confidence: 75%
“…Hypothyroidism causes changes in the handling of long chain fatty acids by white and brown adipocytes. In brown adipocytes fatty acid synthesis from glucose is substantially enhanced in hypothyroidism [25]. In this study, the large clear vacuoles seen in the cytoplasm of brown adipose tissue in the rats were consistent with lipid storage vacuoles, which in turn was consistent with enhanced fatty acid synthesis.…”
Section: Discussionsupporting
confidence: 75%
“…In vivo, lipogenesis is usually highest in hypothyroid BAT and is reduced by T3 treatment (14)(15)(16). Expression of ACC, FAS, and S14 mRNAs follows the same pattern (25).…”
Section: The Effects Of Increasing Glucose Concentrationmentioning
confidence: 94%
“…Numerous studies have indicated that hypothyroidism is a risk factor for nonalcoholic fatty liver disease and results in metabolic syndrome ( 32 34 ). In addition, the effects of hypothyroidism to enhance lipogenesis is amplified in the presence of physiological concentrations of fatty acids ( 35 ). FASN is an enzyme involved in fatty acid biosynthesis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%